Pengaruh Persepsi Budaya Organisasi dan Job Demands Terhadap Workplace Incivility pada Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Dumai, Provinsi Riau - Desvi Emti; Maha Suci Anuggrah; Fatmawati (Al-Manar Journal of Economic and Social Studies, 2025)
This research was conducted on employees of the Population and Civil Registration Services Of Dumai City, Riau Province. The aim of this research is to analyze the influence of organizational culture and professionalism on work incivility among Population and Civil Registry employees in Dumai City District. The data collection technique uses a questionnaire. The type used in this research is the quantitative type regarding the influence between variables. Research data was analyzed using SPSS version 23. The sample in this study were 32 employees of the Dumai City Population and Civil Registry Service using the purposive sampling method. The data analysis used in this research is quantitative using the multiple linear regression method. Based on the research results, it shows that Organizational Culture and Job Demands influence Workplace Incivility both partially and simultaneously. The results of the Coefficient of Determination (R2) show that the influence of the two independent variables together on the dependent variable is 53,9%. Meanwhile, the remaining 46,1%  was influenced by other variables not observed in this study.